2000
DOI: 10.1016/s0014-5793(00)01569-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential incorporation of 1‐β‐D‐arabinofuranosylcytosine and 9‐β‐D‐arabinofuranosylguanine into nuclear and mitochondrial DNA

Abstract: The anti-leukemic nucleoside analogs 1-L L-D-arabinofuranosylcytosine (araC) and 9-L L-D-arabinofuranosylguanine (araG) are dependent on intracellular phosphorylation for pharmacological activity. AraC is efficiently phosphorylated by deoxycytidine kinase (dCK). Although araG is phosphorylated by dCK in vitro, it is a preferred substrate of mitochondrial deoxyguanosine kinase. We have used autoradiography to show that araC was incorporated into nuclear DNA in Molt-4 and CEM T-lymphoblastoid cells as well as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The relative rates of these diverse processes provide at equilibrium a much higher specific radioactivity for mt dGTP than for cytosolic dGTP. This probably explains why in previous autoradiographic experiments (35,36) deoxynucleosides phosphorylated by mt kinases preferentially labeled mt DNA.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The relative rates of these diverse processes provide at equilibrium a much higher specific radioactivity for mt dGTP than for cytosolic dGTP. This probably explains why in previous autoradiographic experiments (35,36) deoxynucleosides phosphorylated by mt kinases preferentially labeled mt DNA.…”
Section: Discussionmentioning
confidence: 76%
“…For a long time the prevailing view was that specific kinases inside mitochondria form mt dNTPs, whereas de novo synthesis by ribonucleotide reductase provides cytosolic dNTPs, with the two pools separated by the mt membrane. Autoradiographic observations (35,36) had shown specific labeling of mt DNA from deoxynucleosides, and metabolic experiments claimed depletion of cytosolic but not of mt dTTP after inhibition with amethopterin (37). Support also came from the discovery that in humans genetic deletion of intra-mt deoxynucleoside kinase activity results in depletion of mt DNA (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the combination of nucleoside analogues with gold(I) might be beneficial in eliminating resistance and delayed toxicity [15,16]. An azole -platinum compound displaying in vitro anticancer activity comparable to that of cisplatin is only slightly more active against cisplatin-resistant cancer cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…It was not very surprising that nelarabine and fludarabine showed unaltered sensitivity in the cells since nelarabine is also efficiently activated by the mithochondrial enzyme deoxyguanosine kinase (Zhu et al 2000) and that resistance mechanismsm against fludarabine has been shown to include altered activity of the ribonucleotide reductase enzyme rather than decreased dCK activity (Mansson et al 2003). During these experimental conditions both deoxyguanosine kinase and the ribonucleotide enzyme seemed unaffected by the dCK downregulation, which probably is one of the reasons for the sustained cytotoxicity of nelarabine and fludarabine.…”
Section: Discussionmentioning
confidence: 93%